(untitled) (Oratio Directa, 2025)
This conceptual-descriptive study discusses corruption, the Mental Revolution program, and rent-seeking practices in the Indonesian bureaucracy. It uses a qualitative literature-based approach and illustrates the discussion with publicly reported corruption cases involving tax and customs officials. The analysis describes the Mental Revolution as an intended transformation from a service-demanding, unproductive, and corrupt bureaucracy toward a serving, productive, clean, and professional administration. It argues that persistent corruption, abuse of authority, procurement manipulation, and rent seeking indicate a gap between these normative goals and bureaucratic practice. Consumer culture and status-oriented lifestyles are proposed as factors that may intensify material incentives among officials. However, the study does not provide a systematic case sample, program indicators, implementation data, interviews, or longitudinal evidence. The reported cases therefore illustrate corruption risks but cannot independently establish the nationwide failure of the Mental Revolution or a causal relationship between consumer culture and corruption. The study concludes that bureaucratic reform requires transparent procurement, asset and conflict-of-interest controls, enforceable sanctions, measurable service standards, institutional oversight, and evaluation based on documented outcomes.